The real sector of Ukrainian economy capitalization: trends and consequences - ZYMOVETS, Vladyslav; BAGATSKA, Kateryna (Scientific journal «World of Finance», 2019)
Introduction. The main trends in the corporate finance of Ukraine hardly could be explained with the traditional corporate finance frameworks which the trading-off or pecking order approaches included. In the beginning of 2017, the whole corporate sector indebtedness (calculated as total unconsolidated debt to book value based equity ratio) was substantially higher than a proper level for emerging markets countries. The restoring of the real sector equity capital sufficiency is crucial for the whole financial system stabilization and investments fostering. Purpose. The investigation of the book value decapitalization in real sector of Ukrainian economy scale and its potential impact on the financial system stability and economic growth assessment. Methods. International comparisons of the total book value capital to GDP ratios, the real book value capital (denominated by GDP deflator) trends and structural changes investigation. Results. The volume and the dynamics of the book value capitalization in Ukrainian economy’s real sector are investigated. The overall level of capital losses is determined (18% decline with 5 years) and significant structural imbalances are revealed. The trends of real sector book value equity changes analyzed comparing with the nominal GDP changes trends in Ukraine and foreign countries. A comparative analysis trends of real sector capital return in Ukraine and some European countries is conducted. The total book value capital to GDP ratio in Ukraine does not differ significantly from other countries. We explain these results capital by the low level of GDP in Ukraine and not by the book value capital sufficiency. The low level of legal productivity the real sector aggregate equity capital in Ukraine is determined. The share of accumulated capital in real sector book value equity in Ukraine was closed to 0 and fall negative in 2017. We explain this by the low level of legal productivity of equity capital in Ukraine. Conclusion. The capital accumulation in the real sector of Ukrainian economy is structurally deteriorated and generates significant risks for the stability of ountry financial system. The lack of capital in real sector hardly can be compensated by the financial sector and government investments. Thus, we can conclude that deficiency of equity in real sector is a strong barrier for the economic growth.